APLIKASI TEMA DESAIN RUMAH SAKIT IBU DAN ANAK BERDASARKAN KARAKTER PENGGUNA RUANG - Latifah Utary; Setiamurti Raharadjo; Doddy Friestya Asharsinyo (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Other than as a means of serving the special health examination of the mother during the pregnancy to pre post childbirth and providing service for the health of children, mothers and children's hospital must also pay attention to aspects of psychiatric or psychological patients and patient needs in order to design can support the recovery process. In addition to the need for facilities that can accomodate an entire user activity, its atmosphere also required space can provide a sense of comfort when residing therein. One way to build the desired room atmosphere users by application of the theme on the space. Therefore, the writing aims to determine the themes that correspond to the user's character and how these themes in the determination process. Research carried out using quantitative methods through questionnaires and continued with the qualitative method which will discuss the process of determining the desired theme and the theme of today’s society forinterior Women’s and Children’s Hospital.